2017
DOI: 10.1111/tmi.12849
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli contamination of child complementary foods and association with domestic hygiene in rural Bangladesh

Abstract: Abstractobjective To determine the frequency and concentration of Escherichia coli in child complementary food and its association with domestic hygiene practices in rural Bangladesh.method A total of 608 households with children <2 years were enrolled. We collected stored complementary food samples, performed spot checks on domestic hygiene and measured ambient temperature in the food storage area. Food samples were analysed using the IDEXX most probable number (MPN) method with Colilert-18 media to enumerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 48 publications
7
44
0
Order By: Relevance
“… 67 Multiplex PCR testing of a subset of E. coli -positive food and fly samples from our study found pathogenic E. coli genes in 14% of E. coli -positive food and 2% of E. coli -positive flies. 68 A previous study in rural Bangladesh found that among tubewells with 1–10 MPN/100 mL E. coli (similar to our tubewell E. coli levels), pathogenic E. coli was detected by qPCR in 21%, rotavirus in 57%, Shigella in 7% and Vibrio cholerae in 7% of wells. 69 Another study in a similar Bangladeshi setting found that, while 97% of soil samples were positive for E. coli , only 14% contained pathogenic E. coli detected by multiplex PCR.…”
Section: Resultssupporting
confidence: 88%
“… 67 Multiplex PCR testing of a subset of E. coli -positive food and fly samples from our study found pathogenic E. coli genes in 14% of E. coli -positive food and 2% of E. coli -positive flies. 68 A previous study in rural Bangladesh found that among tubewells with 1–10 MPN/100 mL E. coli (similar to our tubewell E. coli levels), pathogenic E. coli was detected by qPCR in 21%, rotavirus in 57%, Shigella in 7% and Vibrio cholerae in 7% of wells. 69 Another study in a similar Bangladeshi setting found that, while 97% of soil samples were positive for E. coli , only 14% contained pathogenic E. coli detected by multiplex PCR.…”
Section: Resultssupporting
confidence: 88%
“…Bangladesh (Parvez et al, 2017), but not other findings in Bangladesh (Henry et al, 1990) or Thailand (Imong et al, 1995). The corrective measures proposed correspond with previous HACCP analyses in LMICs used to develop food hygiene interventions (Gautam et al, 2017;M.…”
Section: Storage After Feedingsupporting
confidence: 71%
“…Minimal relative reductions in diarrhoeal disease between Treatments 1 and 2 infer a significant role played by food hygiene practices and associated hand washing with soap at critical times. The role of food in diarrhoeal disease transmission has been long recognised [37][38][39][40][41], and a recent WHO report attributed 70% of the burden of foodborne disease to low and middle income countries, with 40% of this burden affecting children under the age of five [2]. Our findings support the growing body of evidence that improving food hygiene practices can play a significant role in reducing diarrhoeal disease in under five populations.…”
Section: Discussionsupporting
confidence: 81%